Assessing EFL Young Learners’ Reading Skill - Sari, Yuliana Ambar (ENGLISH JOURNAL, 2016)
Assessment should be frequently and systematically included into learning and teaching scheme. It should mirror the activities done and experienced in thorough lesson plan and should give very significant assumption to what the students have achieved. In relation to the skill of reading, English for Young Learners (EYL) practitioners still argue about the appropriate ways to develop learners’ reading skill. They have particularly been discussing about its application and assessment toward young learners. This matter still needs comprehensive ideas to be solved. Reading assessment usually retains in traditional way instead of reflecting more in postmodernism point of view. However, some main considerations must be realized and recognized in assessing such skill. This paper is aimed at sorting some theories (Montessori and other experts) and curriculum implication in deciding some activities useful to conduct reading assessment to young learners. This is done by analyzing postmodernism issue. The result shows that there are eight balancing activities which can be done for better reading assessment for kindergarten students.